(untitled) (Религиски дијалог и соработка, 2023)
Attention is being paid to the rise of post-Soviet nationalism, particularly given the conflict in Ukraine. To this end, the present paper examines Russian thought and its relationship to exceptionalism in the context of the post-Revolutionary diaspora. Examining the prevailing approach taken to freedom of thought, in light of Nikolai Berdyaev, Fr. Sergius Bulgakov and other thinkers, a trajectory can be identified that departs from the exceptionalist narrative. In the diaspora, this was accented by emergence in the context of the ecumenical movement and the keenness demonstrated by the emigres, which was fitting to the East / West interaction of the movement. In an important sense, the notion of Sobornost emerged as a sign of the diaspora’s theological development – in light the evolution of the notion and its ecclesiological aspect, but also in the journal by the same name, which was published under the auspices of the Fellowship of St. Alban and St. Sergius. This altogether demonstrates a trajectory of thought that emerged in the diaspora intelligentsia, which stood in opposition to exceptionalism, messianic or nationalist sentiments, inasmuch as it was a inheritor of pre-Revolutionary Russian thought, is a contrast to the post-Soviet milieu.